Adjuvant used in cancer diagnosis - DOUAG , Salah; GUETTAR , Rihane; MANSAR , Amira; KEBAIL , Hakima Supervisor (Sétif 1 University Ferhat Abbas . Faculty of Natural and Life Sciences, 2025)
A section is dedicated This thesis explores in depth the methods of cancer diagnosis, emphasizing the crucial role of modern adjuncts. It begins with an overview of the foundations of cancer biology, including its definition, the differences between normal and cancerous cells, the distinctive characteristics of tumor cells, the classification of cancers, their causes, and their development. to various diagnostic methods, ranging from physical examinations to advanced imaging techniques such as microscopy, ultrasound, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET), as well as diagnostic tests and procedures for tumor biomarker testing. The document then focuses on molecular biomarkers, including DNA methylation, non-coding microRNAs, and protein biomarkers, as well as gene fusions in cancer diagnosis. A significant portion is devoted to contrast agents, detailing modern types (iodine-based, gadolinium, barium sulfate, microbubbles, and nanoparticles) and their clinical applications in radiography, fluoroscopy, CT, MRI, and ultrasound, while addressing safety aspects and adverse reactions. Finally, the thesis explores the emerging use of probiotic microorganisms in disease diagnosis, including cancer detection. This comprehensive study highlights the importance of adjuncts in improving the accuracy and effectiveness of cancer diagnosis, paving the way for innovative and less invasive diagnostic strategies..
تستكشف هذه السيرة الذاتية طرق تشخيصالسرطان بعمق، مع التركيز على الدور الحاسم للمساعدات الحديثة. تم ططلقه من الل عرضتقديمي لساسيات بيولوجيا السرطان، بما في ذلك التعريف، والفروق بين الخليا الطبيعية والسرطانية، والخصائصالمميزة للخليا السرطانية، وتصنيف السرطانات، وأسبابها وتطورها. تم تطوير قسم واحد طلى طرق تشخيصية متنوعة، بما في ذلك الفحصالفيزيائي لتقنيات الصور المتقدمة مثل المجهر، والتصوير المقطعي، وقياس الكثافة المقطعية (CT) والتصوير بالرنين المغناطيسي ، (IRM) والتصوير المقطعي بانبعاث البوزيترونات (PET) ، بالضافة طلى فيما يتعلق بالاتبارات التشخيصية وطجراءات ااتبار العلمات الحيوية للورام. تحتوي الوثيقة على العلمات الحيوية الجزيئية، وتتضمن مثيلة ADN و ،microARN غير مرمزة، والعلمات يتم تكريس جزء كبير من عوامل الحيوية البروتينية، بالضافة طلى جينات الندماج في تشخيصالسرطان التباين، وتفصيل النواع الحديثة (على أساس اليود، الجادولينيوم، كبريتات الباريوم، الفقاعات الدقيقة والجسيمات النانوية) وتطبيقاتها السريرية في التصوير الشعاعي، والتنظير الفلوري، والتصوير المقطعي المحوسب، والتصوير بالشعة تحت الحمراء، والتصوير بالموجات فوق الصوتية، بالضافة طلى الجوانب المنية والصحية. ردود الفعل غير المرغوب فيها. وبالتالي، تستكشف المذكرة الستخدام الناشئ .للكائنات الحية الدقيقة التي تحتوي على البروبيوتيك في تشخيصالمراض، وتتضمن اكتشاف السرطان هذه الدراسة الشاملة تسلط الضوء على أهمية المواد المساعدة في تحسين الدقة وفعالية تشخيص .السرطان، مما يفتح الطريق أمام استراتيجيات التشخيصالمبتكرة وأقل تدالل
Keywords: Cancer diagnosis